KONDISI PENCEMARAN LOGAM BERAT DI PERAIRAN SUNGAI DKI JAKARTA - Yudo, Satmoko (Center for Environmental Technology, 2006)
River is a place where people do their cleaning activities and one of drinking water source and also where we could find fish. But nowadays river condition in JakartaÃ‚Â area are seriously polluted. The reasons of water pollution are not only domestic waste but also from industrial waste, factories take out their waste to the river without proccessing it first. One of the pollution materials is heavy metal which could have bad effect on human body. This paper analyses every element of heavy metal contain on rivers in DKI Jakarta area. Ã‚Â Katakunci : Pencemaran, sungai, logam berat, DKI Jakarta.